Forebrain microglia from wild-type but not adult 5xFAD mice prevent amyloid-β plaque formation in organotypic hippocampal slice cultures - Hellwig, Sabine (Sci Rep, 2015)
The role of microglia in amyloid-β (Aβ) deposition is controversial. In the present study, an organotypic hippocampal slice culture (OHSC) system with an in vivo-like microglial-neuronal environment was used to investigate the potential contribution of microglia to Aβ plaque formation. We found that microglia ingested Aβ, thereby preventing plaque formation in OHSCs. Conversely, Aβ deposits formed rapidly in microglia-free wild-type slices. The capacity to prevent Aβ plaque formation was absent in forebrain microglia from young adult but not juvenile 5xFamilial Alzheimer’s disease (FAD) mice. Since no loss of Aβ clearance capacity was observed in both wild-type and cerebellar microglia from 5xFAD animals, the high Aβ(1−42) burden in the forebrain of 5xFAD animals likely underlies the exhaustion of microglial Aβ clearance capacity. These data may therefore explain why Aβ plaque formation has never been described in wild-type mice, and point to a beneficial role of microglia in AD pathology. We also describe a new method to study Aβ plaque formation in a cell culture setting.